Boosted Hydrogen‐Evolution Kinetics Over Particulate Lanthanum and Rhodium‐Doped Strontium Titanate Photocatalysts Modified with Phosphonate Groups. (14th December 2020) - Kageshima, Yosuke; Kawanishi, Toshiki; Saeki, Daisuke; Teshima, Katsuya; Domen, Kazunari; Nishikiori, Hiromasa
Abstract: Phosphonate groups loaded on the surface of the visible‐light‐responsive photocatalyst Ru‐loaded La, Rh‐doped SrTiO3 (Ru/La, Rh:STO) via a silane‐coupling treatment enhance the photocatalytic activity of this material during the hydrogen evolution reaction. Surface modification with an alkylsilane phosphonate accelerates the supply of reactants to active sites and is much more effective at improving the photocatalytic activity than the utilization of a phosphate‐buffered electrolyte as a reaction solution. In contrast, the incorporation of amine, sulfonate, and propyl groups does not improve the activity. The effects of these functional groups introduced via silane coupling on the reaction kinetics of hydrogen evolution are evaluated separately from the oxidative reaction using electrochemical methods. It was also demonstrated that the present alkylsilane phosphonate modification increases the photocatalytic activity even under a low photon flux. Abstract : Phosphonate groups loaded on the surface of a visible‐light‐responsive photocatalyst via a silane‐coupling treatment enhance the photocatalytic activity during hydrogen evolution by accelerating the supply of reactants. Modification with an alkylsilane phosphonate is much more effective at improving the photocatalytic activity compared to the use of a phosphate‐buffer electrolyte as the reaction solution.